2011
DOI: 10.2165/11592760-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy for Ischemic Cardiovascular Disorders

Abstract: Ischemic heart disease is the leading cause of death and a major cause of hospital admissions, with the number of affected patients increasing worldwide. The current management of ischemic heart disease has three major therapeutic options: medication, percutaneous coronary intervention (PCI), and coronary artery bypass grafting (CABG). However, the prognosis for patients with severe ischemic heart disease without indications for PCI or CABG still remains poor due to the lack of effective treatments. It is ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 64 publications
0
40
0
1
Order By: Relevance
“…[19] It has been proved that L-ESWT treatment of human myocardial tissue undergoing ischemia upregulates the expression of VEGF and induces neovascularization devoid of any adverse effects. [19] A similar restorative effect of L-EWST on the VEGF expression levels was observed in our diabetic rats without any statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…[19] It has been proved that L-ESWT treatment of human myocardial tissue undergoing ischemia upregulates the expression of VEGF and induces neovascularization devoid of any adverse effects. [19] A similar restorative effect of L-EWST on the VEGF expression levels was observed in our diabetic rats without any statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous studies, 7-11, 18 we performed low-energy SW therapy (0.1 mJ/mm 2 , approximately 10% of the energy used for the lithotripsy treatment, 200 shots, 1 Hz, to the whole heart) using a specially designed SW generator equipped with an echocardiographic probe (Storz Medical AG, Kreuzlingen, Switzerland) under inhalation anesthesia with 2% isoflurane. The SW group was subjected to SW therapy 3 times in the first week (1, 3 and 5 days after AMI), whereas the control group underwent the same procedures 3 times including anesthesia but without SW treatment.…”
Section: Extracorporeal Sw Therapymentioning
confidence: 99%
“…First, in the present study, we chose the condition of SW therapy (eg, energy levels, number of shots) based on our previous studies 7-11, 18 and did not test other therapeutic conditions. It is reported to affect the inflammatory state and LV remodeling after AMI.…”
Section: Study Limitationsmentioning
confidence: 99%
“…We have previously demonstrated that low-energy extracorporeal cardiac shock wave therapy improves myocardial ischemia in a porcine model of chronic myocardial ischemia and patients with severe angina pectoris through enhanced myocardial angiogenesis. [4][5][6][7] Recently, we have further demonstrated that low-intensity pulsed ultrasound (LIPUS) therapy also induces angiogenesis and ameliorates myocardial ischemia in a porcine model of chronic myocardial ischemia. 8 LIPUS is also used for the treatment of patients with several diseases in orthopedics, dentistry, and brain stimulation.…”
mentioning
confidence: 99%